Review of Secondary Metabolites From Melandean Bark Extract (Bridellia Micrantha): Bioactive Potential and Applications in Health - Bayani, Faizul; Muhali, Muhali; Yuliana, Devi; Hulyadi, Hulyadi; Gargazi, Gargazi (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Abstract The emergence of various diseases affecting the immune system, such as COVID-19 and Hand, Foot, and Mouth Disease, demands serious attention. Current climate changes occurring in almost all parts of the world can lead to the emergence of various viruses and bacteria that cause multiple diseases. Exploring medicinal plants that can enhance the immune system is crucial to be continued. This study aims to identify secondary metabolite compounds contained in Bridellia Micrantha plants using chemical reagents and gas chromatography-mass spectrometry (GC-MS) instruments. This research is an experimental laboratory study. The variable studied is the content of secondary metabolite compounds. Data were collected using chemical reagents and instruments. The obtained data are described in informative tables and graphs. Based on the identification results using instruments, positive results were found for organic compound groups such as flavonoids, alkaloids, and tannins. GC-MS test results showed that the organic compounds contained in Bridellia Micrantha extract are 43.05% hexadecanoic acid, 21.46% oleic acid, 16% docos-13-enoic acid, 3.89% octadecanal, 1.85% propanediol, and 0.91% trans-phytol. Literature reviews indicate that the organic acids in Bridellia micrantha extract have clinical activities as antioxidants and anti-inflammatory agents, while organic compounds containing hydroxyl groups have clinical activities as anti-cancer agents. Based on these findings, Bridellia micrantha extract has the potential as a medicine that can enhance the body's immunity.